(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
technological development. There can be no doubt that this system introduces a new means of payment, in the form of an electronic purse loaded with electronic units which can be used to transfer funds and fulfil a money obligation. However, describing an electronic purse as a In the past several years, many economists have considered the impact of the digital revolution on the money and banking system, and by extension the macro-economy. Although many of the papers on e-money and e-banking have contained useful insights into these developments, they have also tended to paint an incomplete and even confusing picture. The application of information technology to money and banking raises many interesting questions. But to make further progress in understanding the economic effects, we need to advance in two areas. First, we need to settle on a fundamental set of questions that a theory of electronic money and banking should answer. Second, we must build frameworks that can address the basic questions raised by electronic money and banking. On a national level, studies have proven that the more connected a country’s banks; national assets, financial sector and citizens are to each other and the rest of the world, the more economic prosperity that country enjoys. This research examines how a widespread use of digital money would affect monetary policy. Widespread use of digital money could affect central banks in such areas as monetary policy, banking supervision of the payment system, and the stability of the financial system. The increased use of E-money has lead to various studies about the impact this new form of money could have on central banks’ ability to control the money supply. Many economists believe that E-money could completely replace currency while others feel that its impact will be less drastic. E-money is the newest payment instrument. As a part of the new electronic payment system (possible future substitute of traditional payment), e-money raises the professional interest about its implications to further development of banking functions in the global and networked economy. Statistical evidence confirms the existence of e-money in the developed countries, which is understandable because of their high technological level and knowledge and the ability to absorb useful innovations of any kind. But, although electronic money has been present in their markets for more than 20 years, its use is still at a very low level. The reason could be found in the level of economic and means of payment is not sufficient in itself, bearing in mind that means of payment such as bank notes and coin, cashless payment media like cheques and payment cards, and even debt securities do not have a uniform status and are not governed by a uniform set of rules.